Implementation of the SCAMPER Technique to Create Innovation and Increase the Business Competitiveness of Ardian Collections MSMEs - Sari, Vinna Ardian; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : This study aims to determine the application of the SCAMPER method in the process of innovating dowry and delivery products in Ardian Collections MSMEs, so that it can increase sustainable business competitiveness. Design/Method/Approach : The method used in this study is a descriptive qualitative approach, data collection through interviews, observations, and documentation by applying the 5R (Relevance, Representative, Reliable, Realistic, Robust) informant selection technique. The informants of this study are 3 informants, namely 1 business owner and 2 Ardian Collections consumers. Research Findings : The results of the study show that Ardian Collections has applied SCAMPER elements such as Combine, Modify, and Put to Another Use in its product innovation process. However, other elements such as Substitute, Adaptate, Eliminate, and Reverse have not been utilized to the fullest, due to the constraints of creating innovation from business owners where owners are still hesitant to explore something new. Theoretical contribution/originality : In previous research, not many applied the SCAMPER innovation technique to the MSME sector in the handicraft sector Practical/Policy Implications : Ardian Collections can maximize the elements of SCAMPER that have not been implemented in this case, namely Substitute, Adaptate, Eliminate, and Reverse. Research limitations : The limitation of this research lies in its focus on only one MSME in Kediri City, so the results of the research may not be fully generalized to MSMEs in other areas, so a more comprehensive study is needed. In addition, the data obtained was limited to interviews and observations.